Microclimate Profile of a Naturally Ventilated Dairy Barn and Its Relationship with Behavioral Responses and Performance of Lactating Dairy Cows - A Case Study at Taman Ternak Sapi Perah Pagerkukuh Wonosobo: Profil Mikroklimat Kandang Model Ventilasi Alami dan Hubungannya dengan Respon Tingkah Laku dan Performa Sapi Perah Laktasi - Studi Kasus Kandang Taman Ternak Sapi Perah Pagerkukuh Wonosobo - Labib Abdillah; Galy Hardyta; Dody Houston Bilhaq; Muhammad Arief Ginanjar; Dwiki Ainun Najib; Rizki Muh Afif (Buletin Peternakan Tropis, 2026)
This study aimed to evaluate the microclimate profile of a naturally ventilated dairy barn and its association with behavioral responses, physiological status, and milk production of lactating dairy cows at Taman Ternak sapi perah Pagerkukuh Wonosobo. The study employed a descriptive quantitative approach using a census method on 12 lactating cows over a 14-day observation period. Microclimate variables included air temperature, relative humidity, wind speed, and Temperature Humidity Index (THI), which were recorded at 3-hour intervals. Observations were also conducted on behavioral activities (feeding, drinking, standing, and lying), physiological parameters (respiration rate, pulse rate, and rectal temperature), and daily milk production. The results showed that the average THI inside the barn was 75.15, with an average wind speed of 0.14 m/s and relative humidity of 88.12%. Behavioral patterns indicated increased drinking and standing activities during peak THI periods, accompanied by longer feeding duration. Physiological responses showed an increase in respiration rate, while pulse rate and rectal temperature remained within normal ranges, indicating mild adaptation. Average milk production was 9.3 L/day, with indications of reduced feed utilization efficiency. Based on the findings, naturally ventilated housing was not effective in providing optimal microclimate conditions. Microclimate variations were closely associated with behavioral and physiological responses, with behavior serving as the most sensitive indicator of heat stress.